The impact of ambient air pollution and meteorological factors on emergency hospital admissions of COPD patients in Poland (2012–2019) - Bogdan Bochenek; Mateusz Jankowski; Joanna Wieczorek; Marta Gruszczyńska; Piotr Sekuła; Adam Jaczewski; Andrzej Wyszogrodzki; Jarosław Pinkas; Mariusz Figurski (Scientific Reports)
Abstract The relations between ambient air pollution, meteorological factors, and the number of emergency hospital admissions due to chronic obstructive pulmonary disease (COPD) were analyzed. The study utilized a nationwide collection of emergency hospital admissions from anonymous public registries covering the period of 8 years (2012–2019). Separated analyses were presented by sex, age group, and place of residence (rural vs. urban area), a group of major pollutants (PM2.5, PM10, SO2, NOx, and NO2), and meteorological factors (daily air temperature minimum (Tmin), air temperature maximum (Tmax) and the daily change of an average air temperature (dTc), relative humidity (Rh) and wind speed (Ws)). This analysis confirmed association between environmental factors and an increase in the number of emergency hospital admissions of COPD patients. The greatest correlations (p < 0.001) were r = 0.58 and day lag = 5 days for PM10, r = 0.63 and day lag = 20 days for PM2.5, r = 0.73 and day lag = 20 days for SO2, r = 0.57 and day lag = 25 days for NO2 and r = 0.51 and day lay = 30 for NOx as well as r = -0.78 and day lag = 19 days for Tmax, r = -0.79 and day lag = 19 days for Tmin, r =  − 0.57 and day lag = 22 days for dTc, r = 0.42 and day lag = 30 days for Rh and r = 0.40 and day lay = 14 for Ws. Variations of SO2 and temperature were the most important factors associated with emergency hospital admissions of COPD patients in Poland. Women, patients aged 60–79 as well as inhabitants of urban areas showed stronger and faster responses to changes in environmental elements.